Biodegradation Pathway Of Acid Red 27 By White-Rot Fungus Armillaria Sp. F022 And Phytotoxicity Evaluation - Liyana Amalina Adnan; Tony Hadibarata; Palanivel Sathishkumar; Abdull Rahim Mohd Yusoff (WILEY-VCH Verlag GmbH & Co., 2024)
Indexed by Scopus